2017
DOI: 10.26582/k.49.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the physical working capacity at the fatigue threshold treadmill test

Abstract: The purposes of the present study were twofold: 1) to determine the physical working capacity at the fatigue threshold (PWC FT ) during an incremental treadmill test, and 2) to examine the validity of this fatigue threshold through constant-velocity runs to exhaustion at 90, 100, and 110% of the estimated PWC FT . Twelve aerobically-trained males (mean age±SD=24.6±5.4 years, running volume=69.9±46.0 km·wk -1 , n=9) and females (22.3±2.3 years, 45.6±4.6 km·wk -1 , n=3) volunteered to perform a treadmill test to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that features from an electromyography (EMG) signal can be used to detect fatigue thresholds both during cycling and running [3,4]. The features that have most frequently been used to calculate the fatigue thresholds are amplitude-based measures, such as the root mean square and integrated EMG, and frequency-based measures, such as mean power frequency or median frequency [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that features from an electromyography (EMG) signal can be used to detect fatigue thresholds both during cycling and running [3,4]. The features that have most frequently been used to calculate the fatigue thresholds are amplitude-based measures, such as the root mean square and integrated EMG, and frequency-based measures, such as mean power frequency or median frequency [3].…”
Section: Introductionmentioning
confidence: 99%